Modulation of gut microbiota and short-chain fatty acids by probiotics attenuates inflammation in endometriosis - Dong, Xiaoli; Xie, Fang; Li, Ping (Frontiers in Microbiology, 2026)
IntroductionThis study investigated whether probiotics alleviate Endometriosis (EMs)-related inflammation by modulating the gut microbiota and short-chain fatty acids (SCFAs).MethodsAn endometriosis model was established in SD rats, which were randomly divided into a normal diet group (NCD) and a probiotic group (NCD_Pro), with four rats per group. After a 4-week dietary intervention, serum and fecal samples were collected. Tumor Necrosis Factor (TNF)-α and Interleukin (IL)-6 levels were measured by ELISA, gut microbiota composition was analyzed via 16S rRNA sequencing, and fecal levels of nine SCFAs were quantified using GC–MS.ResultsProbiotic supplementation significantly reduced serum levels of TNF-α and IL-6 (P < 0.05), but did not significantly affect body weight, body length, or lesion volume. Beta diversity analysis revealed significant structural differences in gut microbiota between the two groups (P < 0.05), while alpha diversity showed no significant difference. At the phylum level, probiotic intervention decreased the relative abundance of Firmicutes and increased that of Bacteroidota and Proteobacteria. At the family level, certain bacterial families showed opposite abundance patterns between the two groups. At the genus level, Bifidobacterium and Lactobacillus were significantly enriched in the probiotic group. Microbial co-occurrence network analysis indicated increased node number and connectivity along with enhanced network stability in the probiotic group. SCFA profiling showed decreased levels of butyric acid (BA) and caproic acid (CA), and a significant increase in isocaproic acid (4-MVA) in the probiotic group. Correlation analysis revealed a significant negative association between specific differential microbiota and 4-MVA (r < −0.6, P < 0.01).ConclusionProbiotic intervention alleviates systemic inflammation in endometriosis by reshaping the gut microbiota structure, enhancing microbial network stability, and modulating the SCFA metabolism. Our findings underscore the role of the gut microbiota-metabolism-immunity axis in EMs pathophysiology and point to 4-MVA as a hypothesis-generating candidate metabolite that requires further validation.